ACCRUAL ACCOUNTING BENEFITS: AN EXTENSIVE LITERATURE REVIEW - khoirul aswar (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The purpose of this study is to review scholarly works on accrual accounting's advantages. The advantages of accrual accounting can be divided into six main groups: accountability, transparency, dependability, managers' capacity to evaluate service costs, and more comprehensive and high-quality information. Last but not least, this paper outlines the goals of accrual accounting as well as its significance. The aforementioned research are systematically observed in this investigation. The advantages of accrual accounting are divided into six groups by this study: accountability, openness, dependability, managers' capacity to evaluate service costs, and more comprehensive and high-quality information. According to this study, in order for the government to more effectively implement accrual accounting, it is vital to take into account the factors that influence accrual accounting. The results of this study will help the government, industry, regulators, and scholars better understand the advantages of accrual accounting.